Multinationals, Endogenous Growth and Technological Spillovers: Theory and Evidence - Henrik Braconier; Richard E. Baldwin; Rikard Forslid (The Research Institute of Industrial Economics (IUI), 1999)
FDI has received surprisingly little attention in theoretical and empirical work on openness and growth. This paper presents a theoretical growth model where MNCs directly affect the endogenous growth rate via technological spillovers. This is novel since other endogenous growth models with MNCs, e.g. the Grossman-Helpman model, assume away the knowledge-spillovers aspect of FDI. We also present econometric evidence (using industry-level data from seven OECD nations) that broadly supports the model. Specifically, we find industry-level scale effects and international knowledge spillovers that are unrelated to FDI, but we also find that bilateral spillovers are boosted by bilateral FDI.
Keywords: F12; O32; O41; 330; MNCs; Economic growth; R&D; Auslandsinvestition; Multinationales Unternehmen; Neue Wachstumstheorie; Spillover-Effekt; Innovationsdiffusion; OECD-Staaten